War on the Silver Screen : Shaping America's Perception of History - Jeansonne, Glen, 1946-; Luhrssen, David (Book collections on Project MUSE., 2014)
Americans have been almost constantly at war since 1917. In addition to two world wars, the United States has fought proxy wars, propaganda wars, and a ""war on terror, "" among others. But even with the constant presence of war in American life, much of what Americans remember about those conflicts comes from Hollywood depictions. In War on the Silver Screen Glen Jeansonne and David Luhrssen vividly demonstrate how war movies have burned the images and impressions of those wars onto the American psyche more concretely than has the reality of the wars themselves. That is, our feelings about war.